A Study On The Prevalence Of Diabetic Mellitus And Its Effects Among 60-Year-old Women Of Shankhu, Kathmandu - Shrestha, Rina; Shrestha, Nistha (Journal of Advanced Academic Research, 2025)
Background: Diabetes mellitus is a burgeoning worldwide problem of considerable cultural, well-being, and economic impact. A calculation of two hundred and eighty five million individuals globally, or approximately 6.4% of the adult group, are living with this disease. Fatness and people aging are the major drivers of the increase. Objective: To assess the prevalence of diabetes and analyze the effect of Diabetes on women’s lives Methods: The study was carried out from March to July 2025, and Shankhu, Kathmandu, Nepal, was selected randomly for this research. Over 70 women over the age of 60 who completed usual surveys and used other research tools to have broader knowledge of the risk variables were studied. A mixed-methods approach was applied to analyze the factors associated with diabetes. Results: The data state that the Primary causes of Diabetes are genetic effects, lack of exercise, consumption of calorie-based food, and hectic lifestyles, which are included in the study area. Diabetic patients face a common problem of weight loss, frequent urination, thirst, and blurred vision, chest, heart, and many internal problems related to women. A patient has less interest in physical activity, and many women have stated a situation of fatigue and high stress levels. Conclusion: The study concluded that Diabetes is a disease that causes a series of Problems in human life. To mitigate these health problems, a healthy lifestyle is extremely required to address health problems.